Trà My
10 tháng 7 2017 lúc 23:15

\(A=\frac{1}{x-\sqrt{x}+1}=\frac{1}{x-2.\frac{1}{2}.\sqrt{x}+\frac{1}{4}+\frac{3}{4}}=\frac{1}{\left(\sqrt{x}-\frac{1}{2}\right)^2+\frac{3}{4}}\)

\(\left(\sqrt{x}-\frac{1}{2}\right)^2\ge0\Rightarrow\left(\sqrt{x}-\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}\Rightarrow A=\frac{1}{\left(\sqrt{x}-\frac{1}{2}\right)^2+\frac{3}{4}}\le\frac{4}{3}\)

Dấu "=" xảy ra khi \(\left(\sqrt{x}-\frac{1}{2}\right)^2=0\Leftrightarrow\sqrt{x}-\frac{1}{2}=0\Leftrightarrow\sqrt{x}=\frac{1}{2}\Leftrightarrow x=\frac{1}{4}\)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN